Antibacterial activity of Ocimum gratissimum L. essential oil - Celso Vataru Nakamura; Tania Ueda-Nakamura; Erika Bando; Abrahão Fernandes Negrão Melo; Díogenes Aparício Garcia Cortez; Benedito Prado Dias Filho (Memorias do Instituto Oswaldo Cruz, 1999)
The essential oil (EO) of Ocimum gratissimum inhibited Staphylococcus aureus at a concentration of 0.75 mg/ml. The minimal inhibitory concentrations (MICs) for Shigella flexineri, Salmonella enteritidis, Escherichia coli, Klebsiella sp., and Proteus mirabilis were at concentrations ranging from 3 to 12 mg/ml. The endpoint was not reached for Pseudomonas aeruginosa (>=24 mg/ml). The MICs of the reference drugs used in this study were similar to those presented in other reports. The minimum bactericidal concentration of EO was within a twofold dilution of the MIC for this organism. The compound that showed antibacterial activity in the EO of O. gratissimum was identified as eugenol and structural findings were further supported by gas chromatography/mass spectra retention time data. The structure was supported by spectroscopic methods.